Case Report: Chronic hepatitis E in a hematopoietic stem cell transplant recipient: The first report of hepatitis E virus genotype 4 causing chronic infection in a non-solid organ recipient - Chen, Zihao; Wei, Junfeng; Jiang, Li; Ying, Dong; Tian, Weikun; Zhang, Mengyang; Wen, Guiping; Wang, Siling; Liu, Chang; Wang, Yingbin; Wu, Ting; Tang, Zimin; et al. (Frontiers in Immunology, 2022)
Hepatitis E virus (HEV) is one of the most important public health issues around the world, and chronic HEV infection has been reported in immunosuppressed individuals. This study reported a male case, with very severe aplastic anemia (AA), who developed chronic hepatitis E after hematopoietic stem cell transplantation (HSCT). Abnormal alanine aminotransferase (ALT) appeared after HSCT and persisted for twenty-nine months. The case was seropositive for anti-HEV IgG and IgM after HSCT. Twenty-two months after HSCT, HEV RNA and antigen (Ag) testing were positive and persisted for five and seven months, respectively. Positive stains of HEV Ag were present in a liver biopsy sample. HEV Ag was present in bone marrow. The individual rapidly developed liver cirrhosis and was rescued by a regimen of oral ribavirin. These factors suggested there is a risk of HEV infection in HSCT recipients.